Macroeconomic Factors Affecting Financial Performance in Islamic Banks and Conventional Banks: A Comparative Analysis - Siti Maryama; Berlianingsih Kusumawati; Sulistyo Seti Utami; Ermalina Ermalina; Tatum Artha (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine macroeconomic factors that affect the financial performance of Islamic and conventional banking. This study uses PLS-SEM to determine the macroeconomic factors that affect the performance of Islamic and conventional banking. The data used is secondary data with a time span of 2018-2022 for all Islamic and conventional banks in Indonesia. The results of this study are external macroeconomic factors that significantly affect the financial performance of Islamic banks with a value of 0.000 and conventional banks with a value of 0.000. However, the most influential Islamic bank is the capital adequacy ratio (CAR) with a value of 35.429, while the financial performance factor of conventional banks is the loan to asset ratio (LAR) with a value of 45.177. This research is expected to be an early warning system for Islamic banks and conventional banks in Indonesia.